Empire for liberty: Melville and the poetics of individualism - Dimock, Wai-chee (Princeton University Press, 2021)
Frontmatter -- Contents -- Acknowledgments -- Empire for Liberty -- CHAPTER I: Nation, Self, and Personification -- CHAPTER 2: Author as Monarch -- CHAPTER 3: Author as Subject -- CHAPTER 4: Blaming the Victim -- CHAPTER 5: Knowing the Victim -- CHAPTER 6: Personified Accounting -- Notes -- Index